Vascular density and macular sensitivity in eyes after scleral buckling surgery for macula-on rhegmatogenous retinal detachment - Przemyslaw Zabel; Katarzyna Zabel; Karolina Kazmierczak; Martyna Stankiewicz; Damian Jaworski; Karolina Suwala; Katarzyna Buszko; Joanna Stafiej; Grazyna Malukiewicz; Jakub J. Kaluzny (PLoS ONE, 2023)
Purpose To investigate the structure and function of the retina after scleral buckling (SB) surgery due to macula-on rhegmatogenous retinal detachment (RRD). Methods Twenty eyes with repaired macula-on RRD and 20 fellow eyes were included. All patients within 6–12 months of the procedure, were examined to evaluate retinal structure using spectral domain optical coherence tomography (SD-OCT) and vessel density (VD) by OCT angiography (OCTA). Best corrected visual acuity (BCVA) and microperimetry (MP) tests were used to assess retinal function. Results Analysis of the microvascular network using OCTA between the operated and healthy fellow eyes showed a significant reduction on VD in superficial vascular plexus (SVP), deep vascular plexus (DVP) and radial peripapillary capillaries (RPC) (p< 0.001, p = 0.019 and p = 0.008, respectively). Comparison of retinal structure in SD-OCT showed no significant differences on thickness in ganglion cell complex (GCC) and peripaillary retinal nerve fiber layer (pRNFL) (p> 0.05) between examined eyes. Retinal function analysis by MP examination showed a decrease of retinal sensitivity (p = 0.0013) whereas postoperative BCVA showed no differences (p = 0.62) in the operated eyes. Significant Pearson’s correlations were observed between retinal sensitivity and VD in SVP, RPC (p< 0.05). Conclusion In the eyes after SB surgery due to macula-on RRD, changes in retinal sensitivity were accompanied by impairment of the microvascular network assessed by the OCTA.